Quantum memory using the multi-single-photons storage within a micro-waveguide system for security camera use - Pornsuwancharoen, Nithiroth; Kittisut, Parinya; Kitcharoen, Narawit; Yupapin, Preecha P. (My University, 2011)
We propose a new system of the secret data encoding using a quantum memory that can be formed the high capacity secret codes for camera security. The high capacity encoding is formed by using the spatial mode of the soliton pulse, where the selected output can be stored and the quantum code generated. The perfect security concept by using the single photon property can be used within the embedded device in the camera.
Keywords: Multi-photons; Nano-photonics; Nano-waveguide; Quantum memory; Security camera